The Effectiveness Brand Image And Product Quality On Consumer Purchase Interest In Sidikalang Coffee - idawati purba (Institute of Computer Science (IOCS), 2022)
Coffee is one of the most popular drinks in society. The purpose of this study was to determine and analyze the significant effect of brand image and product quality on consumer buying interest in Kopi TanpakSidikalang. The population in this study are customers or consumers at Kopi TanpakSidikalang in the Dairi area totaling 315 respondents. The sampling technique used in this study is non-probability sampling. The data analysis method used is quantitative method and data analysis method consisting of classical assumption test consisting of normality test, heteroscedasticity test, multiple linear regression test, hypothesis test consisting of t and the f test and the coefficient of determination (R2) test. Work on the data analysis method using the help of SPSS 22 Forwindows. This study concludes that the variables of brand image and product quality have a positive and significant effect on buying interest in Sidikalang Coffee. These results can be seen based on the coefficient of determination test which produces an R square value of 0.973. This shows that the brand image and product quality are able to influence consumer buying interest in Sidikalang Coffee 2.27%.